Ethics and Politics in Early Childhood Education - Dahlberg, Gunilla; Moss, Peter (Contesting Early Childhood, 2005)
The early childhood services of Reggio Emilia in Northern Italy has gained worldwide interest and admiration. Drawing on the ‘Reggio approach’, and others, this book explores the ethical and political dimensions of early childhood services and argues the importance of these dimensions at a time when they are often reduced to technical and managerial projects, without informed consideration for what is best for the child. Extending and developing the ideas raised in Beyond Quality in Early Childhood Care and Education the successful team of authors make a wide range of complex material accessible to readers who may have little knowledge of the various important and relevant areas within philosophy, ethics, or politics, covering subjects such as: post-structural thinkers and their perspectives the history and practice of early childhood work in Reggio Emilia globalization, technological change, poverty, and environmental degradation ethical and political perspectives relevant to early childhood services from Foucault and Deleuze, to Beck, Bauman and Rose. This book presents essential ideas, theories and debates to an international audience. Those who would find this particularly useful are practitioners, trainers, students, researchers, policymakers and anyone with an interest in early childhood education. Peter Moss is Professor in Early Childhood Provision at the Institute of Education, University of London. Gunilla Dahlberg is Professor at Stockholm Institute of Education. She is the leading exponent of the application of post-structural theory to the field of early childhood. 'This book is bold and challenging; it deals with complex ideas and the authors are not afraid to engage with difficult, abstract and complex concepts and apply them directly to practice. By challenging many standard features of existing services the book generates a range of useful insights ... It provides for the practitioner, student or academic who is prepared to invest a little time in getting to grips with its central ideas a compelling vision of an unashamedly utopian model of service provision.' - Journal of Early Childhood Research 1. Opening Narrative 2. Technology as First Practice 3. What Ethics? 4. Preschools as a Loci of Ethical Practice 5. Towards a Pedagogy of Listening 6. Major and Minor Politics 7. The Preschool as a Site for Democratic Politics 8. In Search of Utopia